Adiabatic analysis of microtextured porous journal bearings functioned with power law fluid model. (October 2019) - Sharma, N; Kango, S; Sharma, RK
The present work contributes to a pragmatic approach for improving the performance of porous journal bearings by incorporating different textures. The textures in the form of micro dimples (spherical (Sph) and ellipsoidal (Eps)) were incorporated on the bearing surface, whereas power law fluid was employed as working lubricant of non-Newtonian nature. The permeability effect has been considered through Darcy's equation to derive a modified Reynolds equation. To account for the temperature parameter, the modified energy equation has also been derived for adiabatic conditions and solved numerically. The presence of textures and lubricant rheology influences the load-carrying capacity, coefficient of friction, attitude angle, axial fluid flow, and average temperature of porous journal bearings.